Skin : The complete guide to digitally lighting, photographing, and retouching faces and bodies - Varis, Lee (Wiley Publishing, 2010)
"Revised and thoroughly updated, this practical guide to photographing people is better than ever! What is the color of skin? You may think you know, until you enter the world of digital photography and try to reproduce what you see. Differences in software, lighting, computer calibration--everything has an impact on color. And that's all before you get into differences between people in terms of skin types, ethnicities, age, gender, and more! Hollywood-based photo-illustrator Lee Varis guides you step-by-step through the maze. This new edition covers the very newest trends and techniques in photographing, lighting, and editing skin--and offers plenty of tips, examples, and valuable advice from the author's own professional experience in the field. Shows you how to digitally capture all skin types: male, female, young, old, different skin tones and ethnicities, with makeup or without, wrinkled, tattooed, and more Covers a wealth of topics in addition to photo editing, such as how to obtain model releases and compose shots, how to shoot groups, and how to create promotional headshots Incorporates the latest on working with Photoshop and Lightroom Showcases exceptional work from a variety of photographers and artists If you're photographing people, you'll want this valuable and unique guide on your shelf."--Provided by publisher